Bright Beginnings Project Descriptions - Community Health and Social Services Network (CHSSN) (2019)

Report on the Health and Social Services Priorities of English-speaking Communities in Quebec - Carter, James; Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
In July 2017, the CHSSN submitted the present report to the Quebec Ministry of Health and Social Services inviting it to undertake consultations with key public institutions and community representatives with respect to the recommendations. The objective was to ensure that a proposal to Health Canada reflected the shared commitment of Quebec and its English-speaking communities to work in partnership to improve access to health and social services in English. In its reply to the CHSSN in October 2017 (Appendix), the Ministry supported the recommendations in accordance with comments reflecting the results of its consultations with the public institutions. To support Health Canada in its mandate to prepare a new Contribution Program, the sponsoring organizations of the twenty recognized community health and social services networks along with the CHSSN are submitting the present report and recommendations reflecting the continuity of results of the last federal contribution and emergence of new priorities for the period ahead.
Keywords: Official Language Minority Community (OLMC)